Effects of media coverage on budget transparency in Croatian local administrative units - Ivana Rukavina (Naše gospodarstvo / Our Economy, 2023)
This paper evaluates positive and negative media coverage of online local budget transparency (OLBT) and its impact on budget transparency in Croatian local administrative units in 2018. Using multinomial logistic regression, research confirmed a strong impact of media coverage on budget transparency. Positive media coverage of OLBT increases the probability that local administrative units will attain a higher level of transparency, while negative media coverage is accompanied by a higher likelihood of local units' retention in the lower transparency range. The implications of these findings are clearly emphasized through a deeper understanding of the role of the media in public sector economics, precisely in the context of budget transparency. This study contributes to public sector literature by identifying the effects of positive and negative media coverage on budget transparency.
Keywords: H72; H80; 330; Fiscal transparency; Budget transparency; Local administrative units; Media coverage; Croatia